2012
DOI: 10.1016/j.powtec.2011.11.045
|View full text |Cite
|
Sign up to set email alerts
|

The nature of limestone filler and self-consolidating feasibility—Relationships between physical, chemical and mineralogical properties of fillers and the flow at different states, from powder to cement-based suspension

Abstract: The nature of limestone filler and self-consolidating feasibility Relationships between physical, chemical and mineralogical properties of fillers and the flow at different states, from powder to cement-based suspension. a b s t r a c t Keywords: Powder flow Tribo-electrification Shear of powder Rheological test Kendall's coefficients Wet packing densityThis paper is a part of a large study aimed at identifying the physical and chemical properties of limestone fillers (LF) that govern their behaviour towards s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 15 publications
(31 reference statements)
0
18
0
1
Order By: Relevance
“…In addition, the excessive grinding promotes the formation of electrostatic charges of particles, which produces flocculation. As with the cement case, the phenomenon of over-grinding leads to flocculation phenomena attributed to electrostatic charges, which agglomerate the extremely fine particles (Diederich et al, 2012). In addition, the hydration product of the mechanically activated slag depends not only on the initial specific surface area of the slag but also on the surface activation, as manifested by the change in the zeta potential of the slag during the milling process (Kumar et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the excessive grinding promotes the formation of electrostatic charges of particles, which produces flocculation. As with the cement case, the phenomenon of over-grinding leads to flocculation phenomena attributed to electrostatic charges, which agglomerate the extremely fine particles (Diederich et al, 2012). In addition, the hydration product of the mechanically activated slag depends not only on the initial specific surface area of the slag but also on the surface activation, as manifested by the change in the zeta potential of the slag during the milling process (Kumar et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The following tests were conducted in the different mortars: 4, and voids content as per Equations (5) and (6) for each mortar [38][39][40];…”
Section: Mortar Preparation and Test Conductedmentioning
confidence: 99%
“…Authors of works [3,10] showed a decrease in the yield stress and an increase of plastic viscosity with an increase in the limestone content. The results of tests are usually only related to the chemical and physical properties of limestone, whereas the influence of clinker or Portland cement itself is rarely taken into account [3,8,9,11]. Seeing as rheological properties of the mortars and concrete mixes are important for predicting the workability and workability loss in time, this discrepancy should be a subject of further in-depth research.…”
Section: Introductionmentioning
confidence: 99%